Menuju Surabaya Green City Melalui Kerjasama Kota Kembar Surabaya-Kitakyushu - Widiana, Fany; Utomo, Ario Bimo (Department of International Relations, Brawijaya University, 2021)
The sister city collaboration between Surabaya and Kitakyushu is an example of the active cooperation of local governments in Indonesia. Conceptually, this kind of cooperation is also called paradiplomacy or diplomatic activity carried out by local governments with other regions in foreign countries. This article takes a case study of the sister cities of Surabaya and Kitakyushu to then look at the institutionalization aspect as a dimension that can be seen from paradiplomacy. Using the Surabaya point of view, the institutionalization points that the writer will review in this article are (1) the formation of a special ministry or department; (2) establishment of permanent subnational offices; (3) official visits of regional authorities to foreign territories and countries; (4) participation in various international events organized by foreign actors; (5) formation and participation in multilateral global & cross-border regional networks and working groups in specific fields; and (6) regional authorization participation in international events organized by foreign entities in official delegations of the central government. Keywords: Paradiplomacy, Surabaya, Kitakyushu, Sister City, Institutionalization